The Placebo and Nocebo effect on sports performance: A systematic review. Issue 3 (15th March 2020) - Hurst, Philip; Schipof-Godart, Lieke; Szabo, Attila; Raglin, John; Hettinga, Florentina; Roelands, Bart; Lane, Andrew; Foad, Abby; Coleman, Damian; Beedie, Chris
Abstract: The aim of this review was to determine the magnitude of the placebo and nocebo effect on sport performance. Articles published before March 2019 were located using Medline, Web of Science, PubMed, EBSCO, Science Direct, and Scopus. Studies that examined placebo and nocebo effects of an objective dependent variable on sports performance, which included a control or baseline condition, were included in the analysis. Studies were classified into two categories of ergogenic aids: (1) nutritional and (2) mechanical. Cohen's d effect sizes were calculated from 32 studies involving 1513 participants. Small to moderate placebo effects were found for both placebo ( d  = 0.36) and nocebo ( d  = 0.37) effects and when separated by nutritional ( d  = 0.35) and mechanical ( d  = 0.47) ergogenic aids. The pooled effect size revealed a small to moderate effect size across all studies ( d  = 0.38). Results suggest that placebo and nocebo effects can exert a small to moderate effect on sports performance.